A Prospective Randomized Controlled Study of Endoscopic Sphincterotomy With the Endocut Mode or Conventional Blended Cut Mode. Issue 2 (February 2015) - Tanaka, Yoshiki; Sato, Ken; Tsuchida, Hiroyuki; Mizuide, Masafumi; Yasuoka, Hidetoshi; Ishida, Katsutoshi; Mori, Masatomo; Kusano, Motoyasu; Yamada, Masanobu
<x xml:space="preserve">Abstract</x> Background: Although the potential advantages of the Endocut mode (E-mode) of endoscopic sphincterotomy (EST) over the conventional blended cut mode (C-mode) have been reported, the problems, including the small sample size and retrospective analysis, that occurred in previous studies make it difficult to conclude the advantage of the E-mode regarding the safety and efficacy. We performed a prospective randomized controlled study to compare these modes. Methods: A total of 360 patients with choledocholithiasis or stenosis of the bile duct were randomly assigned to one of the modes. To avoid the technical bias due to multiple operators or institutions, the main operator and the institution were restricted to only one experienced doctor and 3 institutions at his place of employment, respectively. We defined pancreatitis, bleeding, and perforation as complications of EST. Besides, bleeding includes endoscopically evident bleeding that was defined as visible during the procedure of sphincterotomy and temporary slight oozing. Results: The complications occurred in 20 (11.2%) patients from the E-mode group: pancreatitis in 6 (3.4%) and endoscopically evident bleeding in 14 (7.8%). In contrast, the complications occurred in 25 (13.8%) patients from the C-mode group: pancreatitis in 7 (3.9%) and endoscopically evident bleeding in 18 (9.9%), although these findings were not statistically significant. Overall, there were no severe complications. There were no significant differences in completion ratio of EST and the time taken for the sphincterotomy between both groups. Conclusions: The E-mode could not surpass the C-mode in safety and efficacy under the operation by a single endoscopist.